Transobturator suburethral tape versus suburethral tape placement in female stress urinary incontinence - Siu Au, Alejandro (2020)
Introduction: The surgical management of stress urinary incontinence uses the transobturator tape (TOT) technique since 2006. We present a study applying the suburethral tape as a better alternative that does not require the TOT needle. Objective: To demonstrate the advantages of the suburethral tape placement technique over the transobturator tape technique in the surgical treatment of stress urinary incontinence. Methods: Observational comparative study using the noninvasive suburethral tape placement versus the transobturator tape technique. Results: Fifty patients were treated with TOT for stress urinary incontinence and other 50 patients were managed with suburethral tape placement (UTP) in the previous shift the same day or the preceding day. The TOT patients were 56 years old on average, and time of the procedure was 18 minutes on average. Complications included pain in the inguinal area (13 cases), mesh extrusion (2 cases), and suture dehiscence of anterior colporrhaphy, presence of left inguinoperineal granuloma due to mesh reaction and bruising in the left obturator area (one case of each). The 50 patients treated with UTP were 56 years old on average, operating time was 7 minutes on average, and there were no complications. The cost of the TOT kit was about US$ 1 000.00, and the suburethral tape cost was US$ 50.00. Conclusions: In this study of stress urinary incontinence treatment, the suburethral tape technique was safer than the transobturator tape technique and had a lower cost.